2017
DOI: 10.1016/j.biortech.2017.02.126
|View full text |Cite
|
Sign up to set email alerts
|

Dry anaerobic digestion of food waste and cardboard at different substrate loads, solid contents and co-digestion proportions

Abstract: The increasing food waste production calls for developing efficient technologies for its treatment. Anaerobic processes provide an effective waste valorization. The influence of the initial substrate load on the performance of batch dry anaerobic co-digestion reactors treating food waste and cardboard was investigated. The load was varied by modifying the substrate to inoculum ratio (S/X), the total solids content and the co-digestion proportions. The results showed that the S/X was a crucial parameter. Within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Other SSAD studies also concluded that with a low substrate:inoculum ratio (1:3 or up to 25% TS), they obtained a higher methane yield, and low methane yields were observed at higher TS concentrations (Abbassi-Guendouz et al, 2012;Di Maria et al, 2012;Sun et al, 2016;Capson-Tojo et al, 2017). The TS content affects the mass transfer among gasliquid-solid phases and, consequently, the substrate degradation rate.…”
Section: Results Obtained From Central Composite Design For Effect Ofmentioning
confidence: 96%
See 1 more Smart Citation
“…Other SSAD studies also concluded that with a low substrate:inoculum ratio (1:3 or up to 25% TS), they obtained a higher methane yield, and low methane yields were observed at higher TS concentrations (Abbassi-Guendouz et al, 2012;Di Maria et al, 2012;Sun et al, 2016;Capson-Tojo et al, 2017). The TS content affects the mass transfer among gasliquid-solid phases and, consequently, the substrate degradation rate.…”
Section: Results Obtained From Central Composite Design For Effect Ofmentioning
confidence: 96%
“…The low generation of biogas is a consequence of the complex phenomena occurring at high TS concentrations (Capson-Tojo et al, 2017). Abbassi-Guendouz et al (2012) Xu et al (2014) reported a two-sided effect of TS concentration during AD, with an increase of up to 10%(TS) stimulated microbial growth and a consequent increase in methane generation.…”
Section: Introductionmentioning
confidence: 99%
“…One of the alternatives that has been applied to favor the consumption of VFAs in FW AD is the supplementation of trace elements (TEs) . TEs have been found to favor VFA consumption in both mesophilic and thermophilic AD of FW, mainly due to a favored synthesis of critical enzymes in the process of syntrophic hydrogenotrophic methanogenesis (HM), which is known to be the predominant methane‐producing pathway during FW AD . TEs addition has been successfully applied to avoid accumulation of VFAs at high organic loading rates (OLRs) and to recover acidified reactors …”
Section: Introductionmentioning
confidence: 99%
“…to be the predominant methane-producing pathway during FW AD. 2,11,[15][16][17] TEs addition has been successfully applied to avoid accumulation of VFAs at high organic loading rates (OLRs) 10,18,19 and to recover acidified reactors. 20,21 Another strategy to favor VFA consumption during AD that has gained attention in the last few years is the addition of conductive materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation